Divergence between Organometallic and Single-Electron-Transfer Mechanisms in Copper(II)-Mediated Aerobic C–H Oxidation - Suess, Alison M; Ertem, Mehmed Z; Cramer, Christopher J; Stahl, Shannon S (Journal of the American Chemical Society, 2013)
Copper(II)-mediated C–H oxidation is the subject of extensive interest in synthetic chemistry, but the mechanisms of many of these reactions are poorly understood. Here, we observe different products from CuII-mediated oxidation of N-(8-quinolinyl)benzamide, depending on the reaction conditions. Under basic conditions, the benzamide group undergoes directed C–H methoxylation or chlorination. Under acidic conditions, the quinoline group undergoes nondirected chlorination. Experimental and computational mechanistic studies implicate an organometallic C–H activation/functionalization mechanism under the former conditions and a single-electron-transfer mechanism under the latter conditions. This rare observation of divergent, condition-dependent mechanisms for oxidation of a single substrate provides a valuable foundation for understanding CuII-mediated C–H oxidation reactions.